Harmonia i bezinteresowność - antidotum na cierpienie i uzależnienia = Harmony and disinterestedness - an antidote to suffering and addiction - Romanowska-Łakomy, Halina (Zielona Góra: Uniwersytet Zielonogórski)
This article points to the necessity and particularly importence for the development of the teacher's personality. It is taking for granted that the responsable teacher is able to expand the pupil's horizon, deepen his anderstanding and apprecciation and add immeasurably to his mental health and happiness. It depends especially of the teacher's right attitudes. This article is based on opinions many authors and written by utilizing their different works.
Keywords: nauczyciele; rozwój zawodowy